2015
DOI: 10.1111/mmi.13021
|View full text |Cite
|
Sign up to set email alerts
|

Distinct contribution of Toxoplasma gondii rhomboid proteases 4 and 5 to micronemal protein protease 1 activity during invasion

Abstract: SummaryHost cell entry by the Apicomplexa is associated with the sequential secretion of invasion factors from specialized apical organelles. Secretion of micronemal proteins (MICs) complexes by Toxoplasma gondii facilitates parasite gliding motility, host cell attachment and entry, as well as egress from infected cells. The shedding of MICs during these steps is mediated by micronemal protein proteases MPP1, MPP2 and MPP3. The constitutive activity of MPP1 leads to the cleavage of transmembrane MICs and is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 59 publications
(142 reference statements)
0
39
0
Order By: Relevance
“…Following secretion from the micronemes to the parasite plasma membrane, AMA1 is cleaved within its TM domain by the rhomboid protease ROM4 (Rugarabamu et al, 2015; Shen et al, 2014) and its ectodomain released from the parasite. As Cys504 lies within the AMA1 TM domain, we hypothesized that palmitoylation on this site might regulate AMA1 intramembrane cleavage and shedding.…”
Section: Resultsmentioning
confidence: 99%
“…Following secretion from the micronemes to the parasite plasma membrane, AMA1 is cleaved within its TM domain by the rhomboid protease ROM4 (Rugarabamu et al, 2015; Shen et al, 2014) and its ectodomain released from the parasite. As Cys504 lies within the AMA1 TM domain, we hypothesized that palmitoylation on this site might regulate AMA1 intramembrane cleavage and shedding.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in the tail domain of MIC2 and TRAP that are facing the glideosome complex impair the motility of sporozoites and tachyzoites, respectively 85 . However, the deletion of TgMIC2 does not completely abolish motility 23,86 , which suggests that other microneme proteins may participate in gliding.…”
Section: Secretory Organelles Deliver Adhesinsmentioning
confidence: 99%
“…Interestingly, the deletion of TgROM4 has no effect on parasite survival in vitro and is not compensated for by other rhomboid proteases 86,91,92 . However, the non-cleaved ligand-receptor complexes are translocated rearwards and accumulate at the posterior pole of the parasite, leading to tachyzoites exhibiting stationary twirling motility (visualized as upright parasites twirling on their posterior pole; Supplementary information S4 (movie)) instead of productive helical motility (Supplementary information S2 (movie)) 86,92 . The non-cleaved, secreted microneme proteins accumulate on the surface of the parasites, and this results in increased attachment and a defect in apical reorientation.…”
Section: Disengagement Of Adhesive Complexesmentioning
confidence: 99%
“…Indeed, microneme secretion has been demonstrated in several studies to be linked to efficient parasite invasion and gliding motility, and it has been suggested that micronemal proteins act as force transmitters for the acto-myosin system, similar to the role of integrins in amoeboid cells ( Bargieri et al , 2014; Tardieux & Baum, 2016). These proteins are then cleaved by rhomboid proteases (ROMs) to release the force ( Rugarabamu et al , 2015; Shen et al , 2014a). …”
Section: Introductionmentioning
confidence: 99%